Dwelling cells, the city and the autonomy of architecture - Borsi, Katharina (2015)
Hans Scharoun projected his Siedlung Charlottenburg Nord of 1955 and his Siedlung Siemensstadt of 1929 as a partial realization of his urban vision for a radical restructuring of Berlin after WW2. For Scharoun, “the mechanical decentralization” as he paraphrased the bombing of Germany's cities, presented the opportunity to reconstruct a new spatial and social order. His urban figure of a decentralized urban landscape, organized through three parallel bands of development for work, housing and leisure, all connected by transport infrastructure, prescribed the interrelationships between meticulously defined functions. The residential cell, a grouping of around 5000 inhabitants, Scharoun saw as the basis of the ‘structure’ of the ‘new city’ in its mediation between the subject and the metropolis. For Scharoun, Charlottenburg-Nord exemplified how the Gestalt of the scalar relationship between the dwelling, the cell and the city, describe and inscribe a seemingly natural socio-spatial structure conditioning the social and economic equilibrium of the city.